Integrative pan-cancer analysis and experiment validation identified GLS as a biomarker in tumor progression, prognosis, immune microenvironment, and immunotherapy - Dongming Li; Donghui Cao; Yangyu Zhang; Xinyi Yu; Yanhua Wu; Zhifang Jia; Jing Jiang; Xueyuan Cao (Scientific Reports)
Abstract Glutaminase (GLS), a crucial gene regulating glutaminolysis, has received much attention as it was found to regulate tumor metabolism and copper-induced cell death. However, its biological roles and mechanisms in human cancers remain obscure. Consequently, the integrated pan-cancer analyses and biological experiments were conducted to elucidate its oncological functions. We found GLS was differentially expressed in human cancers and upregulated GLS predicted poor survival, clinicopathological progression, and tumor heterogeneity. Single-cell analysis found GLS was closely related to various biological functions and pathways. Spatial transcriptomic analysis found GLS expression was mainly derived from tumor cells, which implies tumor cells may have a stronger ability to utilize glutamine than antitumor immune cells in the tumor microenvironment (TME). Meanwhile, we noticed GLS expression was strongly related to the infiltration of various immune cells and stromal cells, the expression of immunomodulatory genes, the activity of some conventional antitumor agents, and the therapeutic response of immunotherapy. Moreover, enrichment analyses suggested GLS was related to various metabolic reprogramming, innate and adaptive immunity suppression, and extracellular matrix remodeling. Finally, we observed GLS was highly expressed in our gastric cancer (GC) cohort. As an independent risk factor for GC prognosis, high-GLS was closely related to pathological progression. Inhibiting GLS expression in GC cells effectively prevented proliferation, migration, and invasion and triggered apoptosis. In conclusion, GLS is an underlying biomarker for oncological progression, prognosis, TME, antitumor drug sensitivity, and immunotherapy response. Targeting GLS can facilitate the implementation of individualized and combined treatment strategies.